PRODUCTION OF DISPERSED NICKEL POWDER IN ELECTROCHEMICAL PROCESSING OF A RENIUM-CONTAINING HEAT-RESISTANT ALL - O. V. Chernyshova; G. A. Usoltseva; E. G. Baykonurov; D. V. Drobot (Тонкие химические технологии)
The article is devoted to the substantiation of the proposed technological scheme of electrochemical processing of rhenium-containing heat-resistant alloy ZhS32-VI of composition (mass %): Re - 4.0; Co - 9.3; W - 8.6; Y - 0.005; Lа - 0.005; Al - 6.0; Cr - 5.0; Tа - 4.0; Nb - 1.6; Mо - 1.1; С - 0.16; B - 0.15; Cе - 0.025, Ni - 60.05 to obtain nickel-containing cathode deposits. The results of studying the composition, surface morphology and granulometric analysis of cathodic precipitates obtained during the electrochemical processing of the spent heat-resistant alloy ZhS32-VI with the use of acid electrolytes are presented. Anodic dissolution of ZhS32-VI was performed in the galvanostatic mode. The effect of the electrolyte composition on the process parameters (current yield, distribution of alloy components between the electrolysis products, particle size distribution of the cathode product), electrochemical processing of this alloy were established. It is shown that depending on the nature of the electrolyte, cathode deposits of different chemical and phase composition can be obtained. They differ in the size and morphology of the surface. It has been established that the value of the cathode precipitate grains obtained in acid electrolytes is almost the same: 99% of the cathode precipitate grains are in the range from 0.04 to 0.60 μm. The main difference is a slight increase in the amount of fine fraction when sulphosalicylic acid is added to the electrolyte. All the cathodic deposits obtained have a dendritic structure, the development of which depends on the nature of the electrolyte, the precipitates obtained with the use of a nitrate electrolyte having the most developed structure and the smallest particle size.